Lifestyle, high Body Mass Index, and markers of socioeconomic conditions associated with multimorbidity in women - Débora Luiza Franken; Maria Teresa Anselmo Olinto; Juvenal Soares Dias-; Fernanda Souza de Bairros; Vera Maria Vieira Paniz (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: This study aimed to identify the prevalence of multimorbidity and its associated factors in women in southern Brazil. Methods: We conducted a cross-sectional, population-based study with a sample of 1,128 women (age 20-69 years), living in São Leopoldo, southern Brazil. Multimorbidity was defined as two or more chronic conditions measured using the therapeutic and chemical anatomical classification of continuous use medications prescribed by a physician. Poisson regression model with robust variance was used to assess the association between sociodemographic and lifestyle variables and multimorbidity. Results: The prevalence of multimorbidity was 21.7% (95%CI 19.3-24.2), and 26 chronic conditions were identified. A direct linear association was observed with age and income and an inverse association with education. Being unemployed was a risk factor for multimorbidity (PR 1.95; 95%CI 1.51-2.52). Alcohol consumption (moderate or excessive) had a protective effect. Overweight and obese women were 53% (PR 1.53; 95%CI 1.09-2.15) and 76% (PR 1.76; 95%CI 1.27-2.45) more likely to have multimorbidity than eutrophic women. Conclusion: Over 20% of the adult women had multimorbidity, and its occurrence was strongly associated with socioeconomic characteristics, such as fewer years of schooling, higher income, and not having an occupation. The results regarding alcohol consumption are still insufficient to propose a public policy for the prevention of multimorbidity. Excess weight was an independent risk factor and should be addressed in public health policies for the prevention and management of multimorbidity.